Sustainable Cities and the Internet of Things (IOT) Technology: IOT technology improves the development of smart cities’ infrastructures and reduces over-population stresses - Drepaul, Nicole (Consilience, 2020)
In this paper, I aim to understand how IOT technology can improve the development of smart cities’ infra- structures and alleviate the strains of population growth. In order to understand this inquiry, I will begin by defining IOT technology. Then I will examine the function and capabilities of IOT technology and how it helps smart cities’ urban devel- opment in areas such as architectural, agricultural, safety and surveillance, and health and sanitary needs. I will develop a prognosis that provides targeted solutions for how IOT can specifically reduce urban population strains and challenges in particular urban sectors, and analyze the environmental implications of IOT technology. Lastly, in the discussion section, I propose applying sustainable frameworks, that can incorporate IOT technology, and showcase IOT weaknesses. This research concludes with describing the impact of implementing IOT technologies to address specific urban infrastructure and overcrowding problems. It can allow readers to view the interdisciplinary potential of sustainability with the use of technology, environmental science, and engineering, and social science through urban development and planning. Internet of things technology, through a cross disciplinary approach, can alleviate and resolve humanity’s rising problems.